The use of the I3E model in macroeconomic analysis for the Irish economy - Kelly C. De Bruin; Eoin Monaghan; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2020)
The I3E (Ireland Environment, Energy and Economy) model is a single-country, intertemporal computable general equilibrium (CGE) model focusing on environmental policies in Ireland. However, the depth of its modelling, which incorporates the economic interactions between production sectors and other agents, also facilitates its use in wider macroeconomic policy analysis. In the Economic and Social Research Institute (ESRI), there are several macroeconomic models developed and applied to investigate macroeconomic policy issues. These are HERMES (Harmonised Econometric Research for Modelling Economic Systems), COSMO (COre Structural MOdel), and FIR-GEM (Fiscal Irish General Equilibrium Model). As with all economic models, the four models vary in their underlying mechanisms and methodologies, and each model has its associated advantages and disadvantages. The focus of this paper is to show the consistency of the I3E model when compared with these existing models. To do so, we compare the results of four different scenarios, and we find that the results of these shocks when applied to the I3E model are largely in line with the respective results of the other three models. Furthermore, any differences can be explained by the different modelling techniques and/or assumptions. As such, we consider the I3E model to be a reliable tool to be used for both environmental policy analysis, and wider macroeconomic policy analysis on the whole.
Keywords: C61; D15; D25; 330; Model comparison; HERMES; COSMO; FIR-GEM; I3E; CGE modelling